Just Sex: Students Rewrite the Rules on Sex, Violence, Equality and Activism - Gold, Jodi,; Villari, Susan, (Rowman & Littlefield Publishers, 1999)
Armed with three decades of feminism, men and women are coming to college with different ideas and expectations about sexual freedom and violence than did their parents. Since the early 1980's, a student movement has emerged from the belief that sexual violence is neither inherent nor inevitable. Just Sex: Students Rewrite the Rules on Sex, Violence, Equality and Activism chronicles the move to end to all forms of sexual violence and to mold a new sexual paradigm where explicitly consensual sex and sexual autonomy are the norm. Based on ten years of collaborative research and national organizing, Gold and Villari have compiled the writings of leading student activists and young scholars wrestling with complex issues of power inequities, free speech, and societal constructions of gender and sexuality in accessible and mainstream dialogues. Authors also examine the generationally specific style of student activism which emphasizes peer education and institutional collaboration. Just Sex—the first ever gathering of primary documents including university policies, personal testimonies, position papers and scholarly essays—offers a glimpse of the "working papers" of a student movement which has altered the sexual landscape of our campuses and communities forever. This valuable volume will be of interest to student activists, administrators, and anyone interested in ending violence on and off of campus.